Reduced Immune Function and Malnutrition in the Elderly - Abe, Koh; Kadota, Jun-ichi; Shirai, Ryo; Kohno, Shigeru; Kawakami, Kaoru; Iida, Keiko (The Tohoku Journal of Experimental Medicine, 1999)
An important observation in elderly subjects is their susceptibility to infection associated with a decline in host immune function. Nutrition is also an important factor that influences host defense against infection. We, therefore, evaluated the relationship between nutritional status in 155 healthy subjects ranging in age from 20 to 99 years and various immunological parameters, including the phagocytic and bactericidal activities of neutrophils and monocytes, superoxide production and chemotaxis of neutrophils, lymphocyte subsets, blastoid transformation and serum immunoglobulins. Aging was associated with increased phagocytic activity of neutrophils but not bactericidal activity, superoxide production or chemotaxis of neutrophils. Aging was also associated with a significant decrease in the number of lymphocytes as well as a decline in mature T cells and helper/inducer T cells but with increased numbers of activated T cells, suppressor T cells and natural killer cells. In addition, blastoid transformation in response to phytohemagglutinin (PHA) and concanavalin A (Con A) was significantly reduced in aged subjects. A poor nutritional status was noted in individuals 60 years of age or older. The nutritional status did not influence neutrophil function but correlated significantly with the number of lymphocytes and degree of blastoid formation with PHA and Con A stimulation. Our results suggest that the cell-mediated immunity in elderly subjects is reduced as a result of malnutrition, and that improvement of the nutritional status may enhance the immune function, likely contributing to their successful aging.